Huge hepatocellular carcinoma with multiple intrahepatic metastases: An aggressive multimodal treatment. (2015) - Yasuda, Satoshi; Nomi, Takeo; Hokuto, Daisuke; Yamato, Ichiro; Obara, Shinsaku; Yamada, Takatsugu; Kanehiro, Hiromichi; Nakajima, Yoshiyuki
Highlights: To the best of our knowledge, this case was, the largest HCC that had been previously reported to be resected safely. We could avoid spontaneous tumor rupture although its risk was thought to be high. We could control multiple intrahepatic metastases in the remnant liver with repeated TACEs after hepatectomy. Multimodal treatment involving hepatectomy and TACE might be a good treatment strategy. Abstract: Introduction: Huge hepatocellular carcinoma (HCC) possesses a potential risk for spontaneous rupture, which leads to a life-threatening complication with a high mortality rate. In addition, a large HCC is frequently accompanied by intrahepatic metastases. Presentation of case: We describe, the case of a 74-year-old woman with a huge extrahepatically expanding HCC with multiple intrahepatic metastases who was treated by liver resection with repeated transcatheter arterial chemoembolization (TACE). To prevent tumor rupture or bleeding, we performed right hepatectomy. After the operation, TACE was applied for multiple intrahepatic metastases in the remnant liver. Furthermore, the elevated protein induced vitamin K absence (PIVKA II) level had decreased to limits within the normal range. Three months after the first TACE, computed tomography revealed several recurrences in the liver. TACE was applied for the second and third time and the tumors were well controlled. Discussion: Although, liver resection is occasionally performed for patients with huge HCC to avoid spontaneous tumor rupture, only surgical approach might not be sufficient for such advanced HCC. To achieve long-term survival, it is necessary to control the residual intrahepatic tumors. We could control multiple intrahepatic metastases with repeated TACEs after hepatectomy. Conclusion: Multimodal treatment involving hepatectomy and TACE might be a good treatment strategy for patients with huge HCC with multiple intrahepatic metastases if the tumors are localized in the liver without distant or peritoneal metastasis.